2012
DOI: 10.1103/physrevd.85.044011
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting features of anisotropic loop quantum cosmologies: The role of spatial curvature

Abstract: A characteristic feature of loop quantization of the isotropic and Bianchi-I spacetimes is the existence of universal bounds on the energy density and the expansion and shear scalars, independent of the matter content. We investigate the properties of these physical quantities in Bianchi-II and Bianchi-IX spacetimes, which have been recently loop quantized using the connection operator approach. Using the effective Hamiltonian approach, we show that for Bianchi-II spacetime, energy density and the expansion an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
105
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(116 citation statements)
references
References 33 publications
(151 reference statements)
11
105
0
Order By: Relevance
“…It is important to stress that the replacement (3.2) is only valid for spatially flat models, which is our case. When the spatial curvature does not vanish, holonomy corrections have to be introduced in a nontrivial way (see, for instance, [20]). …”
Section: F ðRþ Loop Quantum Cosmologymentioning
confidence: 99%
“…It is important to stress that the replacement (3.2) is only valid for spatially flat models, which is our case. When the spatial curvature does not vanish, holonomy corrections have to be introduced in a nontrivial way (see, for instance, [20]). …”
Section: F ðRþ Loop Quantum Cosmologymentioning
confidence: 99%
“…It is found that GR is an excellent approximation to quantum dynamics at curvature scales small compared to the Planck value, however departures between the two theories become significant in the Planck regime which is described by the effective dynamics to an excellent accuracy. Using effective Hamiltonian method, bounds on expansion and shear scalars have been derived [52,53], and generic results on the absence of strong singularities in isotropic [54,55] and Bianchi-I spacetime [56] have been obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Another important implication results in the form of bounds on physical quantities which appear in geodesic and Raychaudhuri equations. It has been shown that energy density and expansion and shear scalars are bounded for isotropic [45] and anisotropic models [50,47] which has important implications to understand general resolution of singularities. This turns out to be true for isotropic models where it has been demonstrated that there is indeed a generic resolution of strong singularities [45,48].…”
Section: Pos(qgqgs 2011)007mentioning
confidence: 99%
“…The effective dynamics captures the underlying quantum evolution to an excellent accuracy for various models in LQC [11,12,33,28,30,43,44], and has been used to study detailed physical implications of loop quantization of cosmological spacetimes. As an example, using effective spacetime description, singularity resolution in LQC can be understood occurring due to bounds on the growth of spacetime curvature, which plays a conjugate role to geometry [45,46,47], and insights on the generic resolution of strong singularities and geodesic extendability in flat isotropic [45,48] and Bianchi-I models [46] have been obtained. Effective equations have also been used to gain insights on constraining quantization ambiguities [49,50], and have been used to explore the physics of Gowdy models [51].…”
Section: Pos(qgqgs 2011)007mentioning
confidence: 99%
See 1 more Smart Citation